Gender inequality, health expenditure and maternal mortality in sub-Saharan Africa: A secondary data analysis - Frank Chirowa; Stephen Atwood; Marc Van der Putten (AOSIS, 2013)
Background: This article provided an analysis of gender inequality, health expenditure and its relationship to maternal mortality. Objective: The objective of this article was to explore gender inequality and its relationship with health expenditure and maternal mortality in sub-Saharan Africa (SSA). A unique analysis was used to correlate the Gender Inequality Index (GII), Health Expenditure and Maternal Mortality Ratio (MMR). The GII captured inequalities across three dimensions - Reproductive health, Women empowerment and Labour force participation between men and women. The GII is a composite index introduced by the UNDP in 2010 and corrects for the disadavanatges of the other gender indices. Although the GII incorporates MMR in its calculation, it should not be taken as a substitute for, but rather as complementary to, the MMR. Method: An exploratory and descriptive design to a secondary documentary review using quantitative data and qualitative information was used. The article referred to sub-Saharan Africa, but seven countries were purposively selected for an in-depth analysis based on the availability of data. The countries selected were Angola, Botswana, Malawi, Mozambique,South Africa, Zambia and Zimbabwe. Results: Countries with high gender inequality captured by the gender inequality index were associated with high maternal mortality ratios as compared with countries with lower gender inequality, whilst countries that spend less on health were associated with higher maternal deaths than countries that spend more. Conclusion: A potential relationship exists between gender inequality, health expenditure, and maternal mortality. Gender inequalities are systematic and occur at the macro, societal and household levels.